Methods to assess environmental surface disinfectants against viruses: the quest and recommendations for a globally harmonized approach to microbicide testing - Syed A. Sattar; Bahram Zargar; Jason Tetro (Infection Prevention in Practice)
Summary: Viruses pose a wide-ranging and significant risk to human health through acute and persistent infections that may confer risks for sequelae including musculoskeletal, immunological, and oncological disease. Infection prevention and control (IPAC) remains a highly effective, generic, global, and cost-effective means to mitigate virus spread. IPAC recommends proper disinfection of high-touch environmental surfaces (HITES) to reduce the risk of direct and indirect virus spread. The United States, Canada and many other countries mandate pre-market assessments of HITES disinfectants against viruses and other types of microbial pathogens. However, there are basic disparities in the regulation of disinfectants. Such incongruity in test protocols interferes with the determination of the true breadth of the microbicidal potential of a given product in the field where target pathogens are often unknown or may be encountered as mixtures. This review examines the various methodological disparities and recommends a more cohesive and harmonized approach. While there is particular emphasis on viruses here, an overall harmonization in microbicide testing of HITES disinfectants will greatly assist the numerous stakeholders involved in IPAC.